Application of Sufism Values in Building Morals in the Digital Era - Fazjri Ramadhan; Asannudin Asannudin; Ayu Desy Hidayah; Achmad Junaedi Sitika (Interpersonal: Jurnal Bimbingan Konseling Islam, 2026)
This study investigates the role of Sufi values in strengthening virtuous character (akhlak mahmudah) amid the rapid development of the digital era. Using a qualitative approach through literature review and direct observation of current digital behavior, the research explores six key aspects: the core concepts of Sufism as a foundation for soul purification and moral enhancement; the application of Sufi values in everyday digital activities; the contribution of education to moral development in the digital context; the relevance of Sufism in addressing emerging digital challenges; moral issues arising from digital interactions; and spiritual-based solutions to improve self-control and ethical awareness. The findings reveal that Sufi values such as muhasabah (self-reflection), muraqabah (self-monitoring), ikhlas (sincerity), sabr (patience), tawakkul (trust in God), and zuhud (detachment) provide meaningful guidelines for reducing negative behavior in the digital realm, promoting ethical communication, and encouraging wise and responsible use of technology. These spiritual principles assist individuals in navigating digital life with greater awareness, discipline, and integrity. Therefore, Sufism remains a relevant and effective moral framework for confronting ethical challenges and preventing moral decline in the digital age.